National inventory and usage of plant-based medicine to treat gastrointestinal disorders with cattle in Benin - YEDOMONHAN, HOUNNANKPON (My University, 2019)
Gastrointestinal disorders remained recurrent with livestock in Benin despite huge import of veterinary drugs at high costs. Nevertheless, the country abounds rich and varied anti gastrointestinal florawhich are hardly known, neglected and underutilized. The present study investigated the diversity of plants used to treat gastrointestinal disorders and documented the traditional knowledge associated with them. A total of 690 breeders and farmers were interviewed using open-ended and semi-structured interviews. Data were collected on the identity of the informants, plants and plant parts used, gastrointestinal disorders treated and usage types. Data were analyzed through calculation of relative frequency of citation (RFC), and use of descriptive statistics, multivariate analysis, bar charts and balloonplot. A total of 158 medicinal plant species belonging to 60 families and 130 genera were identified. The most represented were Leguminosae (18%) and Combretaceae (6.4%). Thirty-one plant families were mentioned to be highly utilized, among which the most important were Zygophyllaceae, Phytolaccaceae, Rubiaceae, Lamiaceae, Loranthaceae, Thymelaeaceae and Flacourtiaceae. The species were reported to treat seven gastrointestinal disorders. The most frequently cited were intern parasitosis (35%), diarrhea (29%) and constipation (17%). Leaves (40%) and stem barks (28%) are the plant parts mostly used to treat those disorders. The species with the highest value for RFC were: Khaya senegalensis, Anacardium occidentale, Cassia sieberiana, Pterocarpus erinaceus and Vitellaria paradoxa. Socioeconomic factors influencing ethnobotanical knowledge about these specieswere: age, profession and geographic location of the informants. Further analysis of chemical and pharmacological content of those species are necessary to ascertain the efficiency of their claimed properties and relieve farmers of these disorders.
Keywords: Benin; Ethnoveterinary plants; Gastrointestinal disorders; Cattle